2000
DOI: 10.1073/pnas.97.18.10101
|View full text |Cite
|
Sign up to set email alerts
|

Singular value decomposition for genome-wide expression data processing and modeling

Abstract: We describe the use of singular value decomposition in transforming genome-wide expression data from genes ؋ arrays space to reduced diagonalized ''eigengenes'' ؋ ''eigenarrays'' space, where the eigengenes (or eigenarrays) are unique orthonormal superpositions of the genes (or arrays). Normalizing the data by filtering out the eigengenes (and eigenarrays) that are inferred to represent noise or experimental artifacts enables meaningful comparison of the expression of different genes across different arrays in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
1,343
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,744 publications
(1,355 citation statements)
references
References 10 publications
8
1,343
0
4
Order By: Relevance
“…This pattern can be regarded as probe-specific variance, independent of biological samples hybridized to the array. The first PC can be used as a quality control and is named here PCqc (Alter et al, 2000;Sherlock, 2001). PCqc explaining the largest part of the variation could be considered as variation that the arrays have in common (Alter et al, 2000;Crijns et al, 2006).…”
Section: Data Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern can be regarded as probe-specific variance, independent of biological samples hybridized to the array. The first PC can be used as a quality control and is named here PCqc (Alter et al, 2000;Sherlock, 2001). PCqc explaining the largest part of the variation could be considered as variation that the arrays have in common (Alter et al, 2000;Crijns et al, 2006).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…The first PC can be used as a quality control and is named here PCqc (Alter et al, 2000;Sherlock, 2001). PCqc explaining the largest part of the variation could be considered as variation that the arrays have in common (Alter et al, 2000;Crijns et al, 2006). We calculated correlations with PCqc (factor loadings) for each individual array.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Principal components are the orthogonal linear combinations of the genes showing the greatest variability among the cases. The principal components are sometimes referred to as singular values (Alter et al, 2000). Using principal components as predictive features provides a vast reduction in the dimension of the expression data, but has two serious limitations.…”
Section: Class Prediction Algorithms Feature Selectionmentioning
confidence: 99%
“…In a related study, Vicente et al [53] found that the most influential part on the performance of ICA is the whitened transformation. Various other authors pointed the feasibility of whitening as a pre-processing step in microarray data analysis [55][56][57][58][59][60][61]. Whitening is performed via singular value decomposition (SVD) on the centered 3 data matrix X:…”
Section: Compaction Stagementioning
confidence: 99%